Feasibility of single-cell analysis of model cancer and foetal cells in blood after isolation by cell picking - Julie Smith; Andreas Frøslev Mathisen; Nadja Funch Richardt; Ann-Sophie Vander Plaetsen; Filip Van Nieuwerburgh; Henrik Stender; Thore Hillig (Tumor Biology)
The objective of the present feasibility study was to transfer single cell line cells to either microscopy slides for downstream immune characterization or to polymerase chain reaction tubes for downstream DNA quantitation. Tumour cell lines, SKBR3 and MCF7 and trophoblast cell line JEG-3 were spiked in healthy donor blood. The CytoTrack system was used to scan the spiked blood samples to identify target cells. Individual target cells were identified, picked by use of a CytoPicker and deposited to either a microscopic slide or a polymerase chain reaction tube (PCR). Single tumour cells on microscopic slides were further immunostained with human epidermal growth factor receptor 2 (Her2) and epithelial cell adhesion molecule (EpCAM). From the picked cells in polymerase chain reaction tubes, DNA was amplified, quantified and used for Short Tandem Repeat genotyping. Depositing rare cells to microscopy slides was laborious with only five cells per hour. In this study with a trained operator, the picked cells had an 80.5% recovery rate. Depositing single trophoblast cells in PCR tubes was a faster process with 10 cells in 5 min. Immunostaining of isolated cells by both Her2 and EpCAM was possible but showed varying staining intensity. Presence of trophoblasts and contaminating white blood cells in PCR tubes after cell picking was confirmed based on DNA yield and mixed Short Tandem Repeat profiles in five out of eight samples. Using the CytoPicker tool, single tumour and trophoblast cells were successfully isolated and moved from blood samples, allowing subsequent immunostaining or Short Tandem Repeat genotyping.